Simulasi 3 Dimensi Terjadinya Kecelakaan Lalu Lintas Berbasis Web - Ikhwan, Ahmad; Zuhri, Khozainuz; Alfakhri, Raihan (Universitas Mitra Indonesia, 2024)
Motorized vehicles are one of theimportant means of transportation for human life to facilitate various daily activities.in addition, motorized vehicles can also have a negativeimpact on humans, namely traffic accidents that resultin physical disabilities, material losses, and even death. The police, as the party with the authority, wants to make efforts to create safe and orderly traffic, by wanting to hold socializationin the form of electronic media, for example through public service advertisements about traffic rules. However, thereis still a lack of facilities andinfrastructure that support the police to socialize what factors can cause traffic accidents, and theimportance of safetyin driving, moreover, people still don't know about the dangers of driving without safe equipment and thereis still a lack of public awareness of order and safetyin driving. traffic. Thisis the main obstaclein realizing the goal of this socialization.